The significance of the Joint Declarations on freedom of expression. Issue 2 (June 2019) - Parmar, Sejal
This article examines the 'Joint Declarations on freedom of expression' from a critical perspective. Since 1999, these Joint Declarations have been adopted annually by the four intergovernmental mechanisms on freedom of expression with the assistance of two non-governmental organisations. This article identifies the factors which contribute to the Joint Declarations' value, with a specific focus on the collaborative process leading up to their adoption, their progressive content and their demonstrated influence upon courts and other actors. It also acknowledges the limitations of the texts, including their non-binding nature as soft law, their limited impact and lack of visibility. Notwithstanding these issues, this article contends that the Joint Declarations constitute a distinct and potentially influential body of international soft law on freedom of expression, one whose relevance to policy debates deserves broader recognition.